A wear-resistant and corrosion-resistant polyurethane material and preparation method thereof
By mixing chromium nitride and nickel oxide and performing high-temperature roasting, combined with the addition of carbon fiber, modified fillers and corrosion-resistant agents, the problem of insufficient durability of polyurethane materials in terms of wear and corrosion is solved, and the wear resistance and corrosion resistance of polyurethane materials are achieved. Significant improvement in corrosion resistance.
Patent Information
- Application Number
- CN202411451105.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-17
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-10-17
AI Technical Summary
The existing polyurethane materials have insufficient durability in wear and corrosion, making it difficult to meet the application needs in various fields.
By combining chromium nitride with nickel oxide mixed with high temperature roasting, the volatile components are removed and the purity and hardness of chromium nitride are improved. At the same time, the carbon fiber, modified filler and corrosion resistance are added to enhance the wear resistance and corrosion resistance of the material.
It significantly improves the abrasion resistance and corrosion resistance of polyurethane materials, prolong the service life of the material, and shows higher durability in a variety of corrosive environments.
Smart Images

Figure SMS_1 
Figure SMS_2
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of polyurethane materials and relates to a wear-resistant and corrosion-resistant polyurethane material and a preparation method thereof. Background Art
[0002] Polyurethane has a soft and hard segment copolymer structure. This unique structure makes polyurethane products have excellent comprehensive mechanical properties, such as good mechanical properties, aging resistance, oil resistance, and a wide range of adjustable hardness. In recent years, research on the preparation of polyurethane composites using organic or inorganic fillers has received increasing attention.
[0003] Therefore, it is necessary to develop a wear-resistant and corrosion-resistant polyurethane material to meet the requirements of various fields. Summary of the invention
[0004] The purpose of the present invention is to provide a wear-resistant and corrosion-resistant polyurethane material and a preparation method thereof. The prepared polyurethane material has excellent wear resistance and corrosion resistance.
[0005] The purpose of the present invention can be achieved through the following technical solutions:
[0006] A wear-resistant and corrosion-resistant polyurethane material comprises the following raw materials in parts by weight:
[0007] 100-150 parts of polyol, 50-65 parts of isophorone diisocyanate, 10-15 parts of 2,2-dimethylol propionic acid, 1-2 parts of catalyst, 8-12 parts of chain extender, 4-8 parts of triethanolamine, 2-5 parts of carbon fiber, 5-10 parts of modified filler, 2-5 parts of corrosion inhibitor, 3-6 parts of coupling agent, 1-3 parts of foaming agent and 1-3 parts of foam stabilizer;
[0008] The preparation process of the corrosion resistant agent is as follows:
[0009] 50-60 parts of chromium nitride are ball-milled at a speed of 400 r / min for 2-4 hours to obtain chromium nitride powder, and then 10-20 parts of nickel oxide are added, the mixture is stirred evenly, and then put into an atmosphere furnace, and roasted at 800-1000° C. for 3-5 hours. After the roasting is completed, it is naturally cooled to room temperature, and finally the obtained product is aged at 50-60° C. for 40-45 hours to obtain the corrosion resisting agent.
[0010] As a preferred technical solution of the present invention, the preparation process of the modified filler is as follows:
[0011] Put 20-40 parts of calcium carbonate, 1-2 parts of deionized water and 3-5 parts of surfactant into a mixer and stir at a speed of 700-800 r / min for 20-35 minutes, then add 20-30 parts of titanium carbide and continue stirring for 2-3 hours. After stirring, grind in a ball mill at a speed of 400 r / min for 3-5 hours and pass through a 200-mesh sieve to obtain a mixed powder;
[0012] Dopamine was dissolved in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2-3 mg / L, and the mixed material powder was added and mixed evenly, wherein the solid-liquid ratio of the mixed material powder to the mixed solution was 1:20 g / mL, and then a 30% ammonia aqueous solution was added to adjust the pH of the mixed solution to 8.5, and the mixture was stirred at 25-35° C. for 20-24 hours. After filtering, the obtained solid was vacuum dried at 60-80° C. for 8-13 hours to obtain the modified filler.
[0013] As a preferred technical solution of the present invention, the coupling agent is one of KH550, KH560 and KH570.
[0014] As a preferred technical solution of the present invention, the foaming agent is one or more of azobisisobutyronitrile, diisopropyl azodicarboxylate and diethyl azodicarboxylate.
[0015] As a preferred technical solution of the present invention, the foam stabilizer is one of polydimethylsiloxane and Y-10366.
[0016] As a preferred technical solution of the present invention, the surfactant is a mixture of sodium lauryl sulfate and dodecyl dimethyl betaine in a mass ratio of 1:1.
[0017] A method for preparing a wear-resistant and corrosion-resistant polyurethane material, comprising the following preparation steps:
[0018] S1. According to weight proportions, under nitrogen protection, polyol, isophorone diisocyanate and 2,2-dimethylol propionic acid were fully mixed, and then a catalyst was added. The mixture was heated to 80-90°C and stirred for 4-6 hours. After the temperature was lowered to 50-70°C, a chain extender and triethanolamine were added and stirred for 20-40 minutes.
[0019] Then add carbon fiber, modified filler and corrosion resistant agent and stir at a speed of 1000-1500 r / min for 0.5-1 h, continue to add coupling agent, foaming agent and foam stabilizer, stir for 1-2 h under the conditions of vacuum degree less than -0.09 MPa and temperature of 40-55° C. to obtain the wear-resistant and corrosion-resistant polyurethane material.
[0020] As a preferred technical solution of the present invention, the catalyst is one of diisobutyltin dilaurate, stannous octoate and stannous oleate.
[0021] As a preferred technical solution of the present invention, the polyol is one of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol.
[0022] As a preferred technical solution of the present invention, the chain extender is one of 1,4-butanediol and 1,6-hexanediol.
[0023] In the present invention, chromium nitride is mixed with nickel oxide and calcined at high temperature to remove volatile components in the chromium nitride, thereby improving the purity of the chromium nitride, and the calcination process can promote the densification of the internal structure of the chromium nitride, thereby improving its hardness and wear resistance; at the same time, nickel oxide can further enhance the chemical stability of chromium nitride. Chromium nitride itself has good passivation ability and can form a dense passivation film on the surface. The stability of this passivation film can be further enhanced by adding nickel oxide, so that it can heal faster after being damaged, continuously provide protection for the polyurethane material, and more effectively prevent corrosive media (such as moisture, oxygen, acid and alkali solutions, etc.) from contacting the polyurethane material. This enhanced barrier effect can significantly improve the durability of the material in a variety of corrosive environments and extend the service life of the material.
[0024] In the present invention, the anionic surfactant sodium dodecyl sulfate is mixed with the zwitterionic surfactant sodium dodecyl sulfate, which can improve the surface activity of the mixed system, and enhance the dispersibility and wetting ability. The surfactant is used to treat calcium carbonate, and the surfactant can be adsorbed on the surface of the calcium carbonate particles to form a stable molecular film, which can change the surface of the calcium carbonate from hydrophilic to lipophilic, thereby improving the compatibility of calcium carbonate with the polyurethane matrix; at the same time, the surfactant can reduce the surface energy between the calcium carbonate particles, reduce the agglomeration phenomenon between the particles, and improve the dispersion uniformity between the calcium carbonate and the titanium carbide particles and in the polyurethane matrix.
[0025] Dopamine undergoes a self-polymerization reaction under alkaline conditions to generate polydopamine on the surface of the filler. Polydopamine has good adhesion and can form a strong adhesive film on the surface of the filler. It can firmly adhere to the surface of the polyurethane material, thereby increasing the bonding force between the filler and the polyurethane material and improving the overall stability of the material. At the same time, the filler modified by polydopamine can effectively resist external mechanical wear due to the formation of a solid protective layer on the surface, further improving the wear resistance of the polyurethane material.
[0026] Beneficial effects of the present invention:
[0027] In the present invention, polyol reacts with isophorone diisocyanate, and under the action of a catalyst, reacts with a chain extender and a cross-linking agent, triethanolamine, to generate polyurethane, and carbon fibers are added therein to interweave with the polyurethane to improve the wear resistance of the polyurethane, and the wear resistance and corrosion resistance of the polyurethane material are further improved by adding modified fillers and corrosion resistance agents, and a polyurethane material with excellent wear resistance and corrosion resistance is obtained by adding other additives. DETAILED DESCRIPTION
[0028] In order to further illustrate the technical means and effects adopted by the present invention to achieve the predetermined invention purpose, the specific implementation methods, structures, features and effects of the present invention are described in detail below in combination with the embodiments.
[0029] In the following examples and comparative examples:
[0030] The surfactant was a mixture of sodium dodecyl sulfate and dodecyl dimethyl betaine in a mass ratio of 1:1, both purchased from Shanghai MacLean Biochemical Technology Co., Ltd.;
[0031] Chromium nitride: purchased from Shanghai Gelin Technology Co., Ltd.;
[0032] Calcium carbonate: purchased from Hubei Xinkang Pharmaceutical Chemical Co., Ltd.;
[0033] Titanium carbide: purchased from Shanghai Liantian Material Technology Co., Ltd.;
[0034] Dopamine: purchased from Hunan Huibaiyi New Materials Co., Ltd.;
[0035] Polytetrahydrofurandiol: purchased from Hubei Yongkuo Technology Co., Ltd.;
[0036] Isophorone diisocyanate: purchased from Shanghai Yien Chemical Technology Co., Ltd., product number: R018211;
[0037] 2,2-Dihydroxymethylpropionic acid: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: B802228;
[0038] Stannous octoate: purchased from Shanghai MacLean Biochemical Technology Co., Ltd., product number: T818482;
[0039] 1,4-Butanediol: purchased from Hubei Guangao Biotechnology Co., Ltd.;
[0040] Triethanolamine: purchased from Shanghai Aladdin Biochemical Technology Co., Ltd., product number: T431269;
[0041] Carbon fiber: purchased from Dongguan Juona New Materials Co., Ltd., model 181;
[0042] KH550: purchased from Shanghai Yuanye Biotechnology Co., Ltd.;
[0043] Azobisisobutyronitrile: purchased from Jinan Huifengda Chemical Co., Ltd.
[0044] Polydimethylsiloxane: purchased from Shanghai Yuanye Biotechnology Co., Ltd.
[0045] Example 1
[0046] Preparation of corrosion resistant agent:
[0047] 55 parts of chromium nitride were ball-milled at a speed of 400 r / min for 3 hours to obtain chromium nitride powder, and 15 parts of nickel oxide were added. The mixture was stirred evenly and put into an atmosphere furnace for roasting at 900° C. for 4 hours. After the roasting, the mixture was naturally cooled to room temperature. Finally, the product was aged at 55° C. for 43 hours to obtain the corrosion-resistant agent.
[0048] Preparation of modified filler:
[0049] 30 parts of calcium carbonate, 1.5 parts of deionized water and 4 parts of surfactant were put into a mixer and stirred at a speed of 750 r / min for 28 minutes, and then 25 parts of titanium carbide were added and stirred for 2.5 hours. After stirring, the mixture was ground in a ball mill at a speed of 400 r / min for 4 hours and passed through a 200-mesh sieve to obtain a mixed powder;
[0050] Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2.5 mg / L, and the mixed material powder was added and mixed evenly, wherein the solid-liquid ratio of the mixed material powder to the mixed solution was 1:20 g / mL, and then a 30% mass fraction of ammonia aqueous solution was added to adjust the pH of the mixed solution to 8.5, and the mixture was stirred at 30° C. for 22 hours. After filtering, the obtained solid was vacuum dried at 70° C. for 10 hours to obtain the modified filler.
[0051] Preparation of wear-resistant and corrosion-resistant polyurethane materials:
[0052] S1. Under nitrogen protection, 120 parts of polytetrahydrofuran diol, 57 parts of isophorone diisocyanate and 12 parts of 2,2-dimethylol propionic acid were fully mixed, and then 1.5 parts of stannous octoate were added, the temperature was raised to 85°C and stirred for 5h, and then 10 parts of 1,4-butanediol and 6 parts of triethanolamine were added after cooling to 60°C and stirring was continued for 30min;
[0053] At room temperature, 3 parts of carbon fiber, 8 parts of modified filler and 4 parts of corrosion-resistant agent were added and stirred at a speed of 1200 r / min for 0.6 h. Then, 4 parts of KH550, 2 parts of azobisisobutyronitrile and 2 parts of polydimethylsiloxane were added and stirred for 1.5 h at a vacuum degree of less than -0.09 MPa and a temperature of 50°C to obtain a wear-resistant and corrosion-resistant polyurethane material.
[0054] Example 2
[0055] Preparation of corrosion resistant agent:
[0056] 50 parts of chromium nitride were ball-milled at a speed of 400 r / min for 2 hours to obtain chromium nitride powder, and then 10 parts of nickel oxide were added. After mixing and stirring evenly, the mixture was put into an atmosphere furnace and roasted at 800° C. for 3 hours. After the roasting, the mixture was naturally cooled to room temperature. Finally, the product was aged at 50° C. for 40 hours to obtain the corrosion-resistant agent.
[0057] Preparation of modified filler:
[0058] 20 parts of calcium carbonate, 1 part of deionized water and 3 parts of surfactant were put into a mixer and stirred at a speed of 700 r / min for 20 minutes, and then 20 parts of titanium carbide were added and stirred for 2 hours. After stirring, the mixture was ground in a ball mill at a speed of 400 r / min for 3 hours and passed through a 200-mesh sieve to obtain a mixed powder;
[0059] Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2 mg / L, and the mixed material powder was added and mixed evenly, wherein the solid-liquid ratio of the mixed material powder to the mixed solution was 1:20 g / mL, and then a 30% mass fraction of ammonia aqueous solution was added to adjust the pH of the mixed solution to 8.5, and the mixture was stirred at 25° C. for 20 hours. After filtering, the obtained solid was vacuum dried at 60° C. for 8 hours to obtain the modified filler.
[0060] Preparation of wear-resistant and corrosion-resistant polyurethane materials:
[0061] S1. Under nitrogen protection, 100 parts of polytetrahydrofuran diol, 50 parts of isophorone diisocyanate and 10 parts of 2,2-dimethylol propionic acid were fully mixed, and then 1 part of stannous octoate was added, the temperature was raised to 80°C and stirred for 4h, and then 8 parts of 1,4-butanediol and 4 parts of triethanolamine were added after cooling to 50°C and stirring was continued for 20min;
[0062] At room temperature, 2 parts of carbon fiber, 5 parts of modified filler and 2 parts of corrosion-resistant agent are added, and the mixture is stirred at a speed of 1000 r / min for 0.5 h. Then, 3 parts of KH550, 1 to 3 parts of azobisisobutyronitrile and 1 part of polydimethylsiloxane are added, and the mixture is stirred for 1 h at a vacuum degree of less than -0.09 MPa and a temperature of 40°C to obtain the wear-resistant and corrosion-resistant polyurethane material.
[0063] Example 3
[0064] Preparation of corrosion resistant agent:
[0065] 60 parts of chromium nitride are ball-milled at a speed of 400 r / min for 4 hours to obtain chromium nitride powder, and then 20 parts of nickel oxide are added. After mixing and stirring evenly, the mixture is put into an atmosphere furnace and roasted at 1000°C for 5 hours. After roasting, the mixture is naturally cooled to room temperature, and finally the product is aged at 60°C for 45 hours to obtain the corrosion resisting agent.
[0066] Preparation of modified filler:
[0067] 40 parts of calcium carbonate, 2 parts of deionized water and 5 parts of surfactant were put into a mixer and stirred at a speed of 800 r / min for 35 minutes, and then 30 parts of titanium carbide were added and stirred for 3 hours. After stirring, the mixture was ground in a ball mill at a speed of 400 r / min for 5 hours and passed through a 200-mesh sieve to obtain a mixed powder;
[0068] Dopamine was dissolved in a Tris-HCl buffer solution with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 3 mg / L, and the mixed material powder was added and mixed evenly, wherein the solid-liquid ratio of the mixed material powder to the mixed solution was 1:20 g / mL, and then a 30% mass fraction of ammonia aqueous solution was added to adjust the pH of the mixed solution to 8.5, and the mixture was stirred at 35° C. for 24 hours. After filtering, the obtained solid was vacuum dried at 80° C. for 13 hours to obtain the modified filler.
[0069] Preparation of wear-resistant and corrosion-resistant polyurethane materials:
[0070] S1. Under nitrogen protection, 150 parts of polytetrahydrofuran diol, 65 parts of isophorone diisocyanate and 15 parts of 2,2-dimethylol propionic acid were fully mixed, and then 2 parts of stannous octoate were added, the temperature was raised to 90°C and stirred for 6h, and then 12 parts of 1,4-butanediol and 8 parts of triethanolamine were added after cooling to 70°C and stirring was continued for 40min;
[0071] At room temperature, 5 parts of carbon fiber, 10 parts of modified filler and 5 parts of corrosion-resistant agent were added, and the mixture was stirred at a speed of 1500 r / min for 1 hour. Then, 6 parts of KH550, 3 parts of azobisisobutyronitrile and 3 parts of polydimethylsiloxane were added, and the mixture was stirred for 2 hours at a vacuum degree of less than -0.09 MPa and a temperature of 55°C to obtain the wear-resistant and corrosion-resistant polyurethane material.
[0072] Comparative Example 1
[0073] The difference between Comparative Example 1 and Example 1 is that nickel oxide is not added to the corrosion resistance agent in Comparative Example 1, and the other operations are the same.
[0074] Comparative Example 2
[0075] The difference between Comparative Example 2 and Example 1 is that no surfactant is added when preparing the modified filler in Comparative Example 2, and the other operations are the same.
[0076] Comparative Example 3
[0077] The difference between Comparative Example 3 and Example 1 is that the modified filler in Comparative Example 3 is not treated with dopamine when preparing the modified filler, and the other operations are the same.
[0078] Comparative Example 4
[0079] The difference between Comparative Example 4 and Example 1 is that the filler in Comparative Example 4 is not modified by surfactant and dopamine, and the other operations are the same.
[0080] Performance Test:
[0081] 1. Wear resistance:
[0082] The mechanical properties and wear resistance of the above Examples 1-3 and Comparative Examples 1-4 were tested. The obtained polyurethane material was molded into a 4 mm thick wear-resistant specimen by a flat vulcanizer. The molding conditions were: temperature 180°C, pressure 15 MPa, and time 8 min. The wear resistance of each wear-resistant specimen was tested using a multifunctional friction and wear tester UMT-TriboLab under a load of 30 N and a rotation rate of 200 r / min. The experimental time was 60 min. The results are shown in Table 1:
[0083] Table 1
[0084]
[0085] 2. Corrosion resistance:
[0086] The tensile strength test refers to GBT1040.5-2008 Determination of tensile properties of plastics. Acid treatment is soaking in 0.5mol / L hydrochloric acid for 72h, and alkali treatment is soaking in 0.5mol / L sodium hydroxide solution for 72h. After acid treatment or alkali treatment, dry and then test the tensile strength. By comparing with the original tensile strength, calculate the change rate. The results are shown in Table 2:
[0087] Table 2
[0088]
[0089] According to the above data, the polyurethane material prepared by the embodiment of the present invention has higher wear resistance, and after acid and alkali treatment, the change rate of the tensile strength of the embodiment is small, indicating that the polyurethane material prepared by the method of the present invention has stronger acid and alkali corrosion resistance.
[0090] The above description is only a preferred embodiment of the present invention and does not limit the present invention in any form. Although the present invention has been disclosed as a preferred embodiment as above, it is not used to limit the present invention. Any technical personnel in this field can make some changes or modify the technical contents disclosed above into equivalent embodiments without departing from the scope of the technical solution of the present invention. However, any brief modifications, equivalent changes and modifications made to the above embodiments based on the technical essence of the present invention without departing from the content of the technical solution of the present invention are still within the scope of the technical solution of the present invention.
Claims
1. A wear-resistant and corrosion-resistant polyurethane material, characterized in that: It includes the following raw materials in parts by weight: 100-150 parts of polyol, 50-65 parts of isophorone diisocyanate, 10-15 parts of 2,2-dimethylol propionic acid, 1-2 parts of catalyst, 8-12 parts of chain extender, 4-8 parts of triethanolamine, 2-5 parts of carbon fiber, 5-10 parts of modified filler, 2-5 parts of corrosion inhibitor, 3-6 parts of coupling agent, 1-3 parts of foaming agent and 1-3 parts of foam stabilizer, wherein the polyol is one of polyethylene glycol, polypropylene glycol and polytetrahydrofuran diol; The preparation process of the corrosion resistant agent is as follows: 50-60 parts of chromium nitride are ball-milled at a speed of 400 r / min for 2-4 hours to obtain chromium nitride powder, and then 10-20 parts of nickel oxide are added, mixed and stirred evenly, and then put into an atmosphere furnace, and roasted at 800-1000° C. for 3-5 hours, and naturally cooled to room temperature after roasting, and finally the obtained product is aged at 50-60° C. for 40-45 hours to obtain the corrosion resisting agent; The preparation process of the modified filler is as follows: Put 20-40 parts of calcium carbonate, 1-2 parts of deionized water and 3-5 parts of surfactant into a mixer and stir at a speed of 700-800 r / min for 20-35 minutes, then add 20-30 parts of titanium carbide and continue stirring for 2-3 hours. After stirring, grind in a ball mill at a speed of 400 r / min for 3-5 hours and pass through a 200-mesh sieve to obtain a mixed powder; Dopamine was dissolved in a Tris-HCl buffer with a molar concentration of 10 mM to prepare a mixed solution with a mass concentration of 2-3 mg / L, and the mixed material powder was added and mixed evenly, wherein the solid-liquid ratio of the mixed material powder to the mixed solution was 1:20 g / mL, and then a 30% mass fraction of ammonia aqueous solution was added to adjust the pH of the mixed solution to 8.5, and the mixture was stirred at 25-35° C. for 20-24 hours. After filtering, the obtained solid was vacuum dried at 60-80° C. for 8-13 hours to obtain the modified filler.
2. The wear-resistant and corrosion-resistant polyurethane material according to claim 1, characterized in that: The coupling agent is one of KH550, KH560 and KH570.
3. The wear-resistant and corrosion-resistant polyurethane material according to claim 1, characterized in that: The foaming agent is one or more of azobisisobutyronitrile, diisopropyl azodicarboxylate and diethyl azodicarboxylate.
4. The wear-resistant and corrosion-resistant polyurethane material according to claim 1, characterized in that: The foam stabilizer is one of polydimethylsiloxane and Y-10366.
5. The wear-resistant and corrosion-resistant polyurethane material according to claim 2, characterized in that: The surfactant is a mixture of sodium lauryl sulfate and dodecyl dimethyl betaine in a mass ratio of 1:
1.
6. A method for preparing the wear-resistant and corrosion-resistant polyurethane material according to any one of claims 1 to 5, characterized in that: The method comprises the following preparation steps: S1. According to weight proportions, under nitrogen protection, polyol, isophorone diisocyanate and 2,2-dimethylol propionic acid were fully mixed, and then a catalyst was added. The mixture was heated to 80-90°C and stirred for 4-6 hours. After the temperature was lowered to 50-70°C, a chain extender and triethanolamine were added and stirred for 20-40 minutes. Then add carbon fiber, modified filler and corrosion resistant agent and stir at a speed of 1000-1500 r / min for 0.5-1 h, continue to add coupling agent, foaming agent and foam stabilizer, stir for 1-2 h under the conditions of vacuum degree less than -0.09 MPa and temperature of 40-55° C. to obtain the wear-resistant and corrosion-resistant polyurethane material.
7. The method for preparing the wear-resistant and corrosion-resistant polyurethane material according to claim 6, characterized in that: The catalyst is one of diisobutyltin dilaurate, stannous octoate and stannous oleate.
8. The method for preparing the wear-resistant and corrosion-resistant polyurethane material according to claim 6, characterized in that: The chain extender is one of 1,4-butanediol and 1,6-hexanediol.
Citation Information
Patent Citations
Preparation method of foamed ceramic for indoor air purification
CN106116672A
Hydrogen-resistance permeation layer on surface of metal hydride and preparation method thereof
CN107043907A